Praktik GHRM (Green Human Resources Management) Pada Industri Manufaktur : Sebuah Review - Intan Rahmi; Asmawati Asmawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
Awareness related to environmental sustainability and sustainable development, has forced companies in the manufacturing industry to apply the concept of environmentally friendly human resource management (GHRM), in an effort to inherit effective environmental management. This review seeks to highlight the concepts and practices of GHRM and the effects on organizational performance that appear in the literature